Determining the Effect of Supplementing Cassia tora Extract on Immunological and Haematological Parameters of Broiler Birds - Jyoti Sahu; Kishori Mohan Koley; Bhishmadev Sahu (Research Aspects in Agriculture and Veterinary Science Vol. 5, 2022)
The effect of supplementing methanolic extract of Cassia tora on immunological and haematological parameters of broiler bird was determined. Day-old broiler birds of Vencobb strain (n = 36) were randomly assigned into 3 treatments with 3 replicates each, 4 birds (2 each for cell mediated and humoral immune response) in each replicate. The birds of group T1 (Control) received basal diet, whereas birds of group T2 (Standard) received an antibiotic (Lincomycin @ 0.05% in feed) in addition to basal diet. The birds of group T3 (Test) received methanolic extract of leaves of Cassia tora (CSE) @ 0.4 g/l in drinking water in addition to basal diet. The treatment was given to birds of all the groups for 6 weeks. Cell mediated immune response was measured by 2, 4-Dinitro-fluorobenzene (DNFB) skin sensitization test whereas humoral immune response was assessed by micro haemagglutination test against sheep red blood cells. The skin thickness of T3 bird (3.41±0.20 mm) was significantly (p\(≤\)0.05) greater than T2 bird (2.92±0.17 mm) followed by T1 bird (2.20± 0.23 mm) at 48 hrs post sensitization. The HA titers was significantly (p\(≤\)0.05) higher in T3 (4.33±0.21) as compared to birds of T2 (3.5±0.22) and T1 (2.17 ± 0.17). The mean TLC in blood samples of birds of Cassia extract treated group (32.83 ± 0.83 thousand/ mm3) was significantly higher (p\(≤\)0.05) than birds of control group (26.17 ± 0.98 thousand/ mm3). Heterophil count of birds of test group (26.00 ± 0.45%) was non-significantly higher than control group (24.66 ± 0.61%).